Paradigma Pendidikan Agama Integratif-Transformatif - Rusydi, Ibnu (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
Education is the process of transforming knowledge to become mature human beings plenary. However, the knowledge that is released from religious values even bring adverse effects, in which the humanity of human demolished. Consequently, the process of transformation must involve two things at once: the knowledge and values. This is called integrative education. This type of education is not a utopian fantasy but a rational necessity that finds justification in philosophical and theological arguments.